Improving of scientific literacy ability using discovery learning model at the seventh grade students of state JHS 3 Ngronggot, Nganjuk-Indonesia - Sri Ratna Dewi; Mumun Nurmilawati; Dwi Ari Budiretnani (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
Country with good education condition can be seen through its citizen scientific literacy. This research aims to improving the students’ scientific literacy ability by using discovery learning model at 7th grade students of State Junior High School 3 Ngronggot, Nganjuk-Indonesia. The instrument in this Kemmis and Taggart Model of Classroom Action Research was an essay test composed based on indicators developed by Gormaly. The results of the research showed that there were improvements on the students’ scientific literacy ability from cycle I to cycle II on six of seven indicators. Those improvements are as follows: Indentifying scientific opinion increased from 0% into 64.52%, reviewing literature effectively increased from 0% into 29.03%, understanding research design and the way how its effect to the finding/discussion increased from 14.29% into 19.35%, making graphic from the data correctly increased from 0% to 58.07%, solving problems using quantitative skill including operating basic statistics increased from 7.14% to 58.07%. However, in making inference, prediction and drawing conclusion based on quantitative data, the improvement was only on the students’ answer that got 1 score, it increased from 7.14% to 77.42%. In addition, for the indicator of understanding and interpreting basic statistic, it decreased from 21.43% to 12.90%.